O wierszach jak abanicos. Hiszpańskie tropy w poezji Alfreda Marka Wierzbickiego - Skała, Agata (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2021)
Poetry by Alfred Marek Wierzbicki emphasises conspicuous travel routes, so poems inspired by particular places are easily extractable. By analysing poetic images showing Spain and Latin American countries, the author discusses the nomadic nature of the works presented and reconstructs the poetic creed of the author of 'Stąd i stamtąd' [From here and there]. Tracing the intertextual relationships inscribed in the works, the researcher explains the symbolic code hidden in the landscapes and spaces of cities. As the author of the fictional figure called “Pan Credo” [Mr Credo], Wierzbicki is a poet focused on the axiological issues connected with the significance of human existence and the sense of one’s own permanence.